Earliest Arrival Flow with Partial Lane Reversals for Evacuation Planning - Pyakurel, Urmila; Dempe, Stephan (International Journal of Operational Research/Nepal, 2019)
Contraflow evacuation planning strategy is very effective and widely accepted approach for the optimal use of available road network in evacuation management that increases the outward road capacities from the disastrous areas with lane (arc) reversals towards the safer places. It is highly applicable for shifting maximum number of evacuees from the disastrous areas to the safer places as quickly and efficiently as possible. We introduce the partial contraflow approach by reversing only necessary arc capacities to solve the earliest arrival contraflow problem with constant transit times and present efficient algorithms. We solve the earliest arrival partial contraflow problem in two terminal general network in pseudo-polynomial time complexity. On two terminal series parallel network, we solve the problem in strongly polynomial time complexity. Moreover, we present a fully polynomial approximation algorithm that solves the earliest arrival partial contraflow problem on two terminal general network in polynomial time. The unused arc capacities are very useful for the logistic and emergency supports to the evacuees at disastrous areas.